The singing of Alicia Maguiña Málaga in “El Veneno” from 1976: An analysis of her vocal style and performance - Salvio Aldana, Josué Daniel (2024)
The contribution presented in this article is the realization of a musical analysis of the style and vocal performance of Alicia Maguiña Málaga in the triste con fuga de tondero “El Veneno”, a piece compiled by the same performer in Piura in 1968, and recorded its first version in 1976, for Odeón–IEMPSA on the LP Te adoro tierra mía (ELD 02.01.538), with the guitar accompaniment of Carlos Hayre. Material that, because it is the closest recording to the date of its compilation, will be used for this analysis. My contribution was: first, analyze the vocal qualities and resources that Alicia Maguiña used in her interpretation; To do this, we had to make a transcription of the audio recorded in 1976 into score, using the Sibelius score editor; where the vocal qualities and resources adopted by the performer were transcribed into musical language and then described in a narrative and graphic way. And second, get closer to the life and artistic training of the performer, to learn about her interpretive style. The most recurrent qualities and resources found throughout the entire piece were: good dosage of air, vocal agility, rhythmic variation, the use of firulete, glissandi (ascending and descending), vibratos, appoggiaturas, a great variety of dynamics, intensities, character and agogic that are appropriately nuanced with the content of the lyrics and the melody; The use of light vibrato at the end of almost all the phrases stands out, this being a flourish widely used in the singing of the tondero. He employs different vocal placements, sometimes with a light color and sometimes with a dark color, and thereby manages to replicate an organic feeling in his performance.